2015
DOI: 10.1073/pnas.1515919112
|View full text |Cite
|
Sign up to set email alerts
|

Breeding signatures of rice improvement revealed by a genomic variation map from a large germplasm collection

Abstract: Intensive rice breeding over the past 50 y has dramatically increased productivity especially in the indica subspecies, but our knowledge of the genomic changes associated with such improvement has been limited. In this study, we analyzed low-coverage sequencing data of 1,479 rice accessions from 73 countries, including landraces and modern cultivars. We identified two major subpopulations, indica I (IndI) and indica II (IndII), in the indica subspecies, which corresponded to the two putative heterotic groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
181
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 189 publications
(194 citation statements)
references
References 45 publications
9
181
1
3
Order By: Relevance
“…The cross-population likelihood method (XP-CLR) was used to identify genetic selection signals. The XP-CLR data for these rice accessions showed that only OsNRT2.3 of the rice nitrate transporter genes was under selection pressure during evolution and was much stronger in Indica II compared with Indica I rice cultivars (29). Our expression data confirm the XP-CLR results, showing that there were two selection patterns in rice; that is, one group of rice cultivars had selection pressure on the expression ratio of OsNRT2.3b to OsNRT2.3a linking with N accumulation, whereas the other group lost this selection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cross-population likelihood method (XP-CLR) was used to identify genetic selection signals. The XP-CLR data for these rice accessions showed that only OsNRT2.3 of the rice nitrate transporter genes was under selection pressure during evolution and was much stronger in Indica II compared with Indica I rice cultivars (29). Our expression data confirm the XP-CLR results, showing that there were two selection patterns in rice; that is, one group of rice cultivars had selection pressure on the expression ratio of OsNRT2.3b to OsNRT2.3a linking with N accumulation, whereas the other group lost this selection.…”
Section: Discussionmentioning
confidence: 97%
“…Our expression data confirm the XP-CLR results, showing that there were two selection patterns in rice; that is, one group of rice cultivars had selection pressure on the expression ratio of OsNRT2.3b to OsNRT2.3a linking with N accumulation, whereas the other group lost this selection. The division of rice cultivars in the responses of OsNRT2.3b and OsNRT2.3a expression to N supply may result from their different growth and cultivation conditions (29).…”
Section: Discussionmentioning
confidence: 99%
“…Higher nucleotide diversity observed among varieties in RP3 indicated an increase in diversity in the primary gene pool as result of recent chickpea breeding programs. Although, recent studies reported modern breeding processes had no significant change in diversity in several crop species535455. The number of selected haplotypes may serve as an indicator for evaluating the breeding potential of varieties to guide more efficient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Indica rice accounts for more than 70% of world rice production (2) and is genetically much more diverse than japonica rice (3). Genomic studies have established that indica rice can be further subdivided into two major varietal groups, indica I and indica II, which have been independently bred and widely cultivated in China and Southeast Asia, respectively (4). Hybrids between these groups usually show strong heterosis, which provided the basis for the great success of hybrid rice in several countries, including China and the United States.…”
mentioning
confidence: 99%